Rallying forces ; OPM blues ; Ivy Violan [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Tackles the protest march from Batac, Ilocos Norte to Manila that ended in violent dispersal. Interview with record artists and producers about original Pilipino music. An interview with Ivy Violan.
Rallying forces (17 min.) -- OPM blues (15 min.) -- Ivy Violan (19 min.)
VHS.
Keywords: Violan, Ivy; Community power -- Philippines -- Batac (Ilocos Norte); Composers -- Philippines -- Interviews; Demonstrations -- Philippines -- Batac (Ilocos Norte); Songs, Philippine